An eoq model with price and time dependent demand under the influence of complement and substitute product’s selling prices - Karaöz, Murat; Eroğlu, Abdullah; Sütçü, Abdullah; Sulak, Harun (Afyon Kocatepe Üniversitesi, İktisadi ve İdari Bilimler Fakültesi Dergisi, 2010)
Demand for a product is affected by its own selling price. In many situations it has also been affected by its Complement’s as well as substitute’s selling prices. This effect can be observed in many retailed items all over the markets. In this paper, we developed finite replenishment inventory model while considering that demand is sensitive to changes in time, its selling price and prices of complementary and substitute good’s. Numerical example and sensitivity analysis have been performed for demand equation parameters.

Bir malın talebi, malın kendi satış fiyatından etkilenmektedir. Çoğu durumda bu talep bu malın tamamlayıcısı ve ikamesi olan malların fiyatından da etkilenmektedir. Bu etki marketlerdeki parekende ürünlerin çoğunda gözlenebilmektedir. Bu çalışmada talebin; zamana, malın satış fiyatına ve tamamlayıcı ve ikame malların fiyatına bağlı olduğu durum için bir ekonomik sipariş miktarı modeli geliştirilmiştir. Talep denklemi parametreleri için sayısal örnekler verilmiş ve duyarlılık analizleri yapılmıştır.
Tamamlayıcı ve ikame malların fiyatı etkisi altında talebin malın satış fiyatı ve zamana bağlı olduğu durum için bir ekonomik sipariş miktarı modeli
Keywords: Eoq; Inventory; Selling Price; Substitute Good; Complement Good